Optimization of Reclamation of Ni(II)-Rich Solutions by γ-Alumina Nanoparticles - Dubey S.; Sharma G.C.; Sharma Y.C. (My University, 2025)
The present work explores the adsorption potential of γ-alumina, a nanoadsorbent for abatement of Ni(II) from aqueous solutions. A response surface methodological approach was adopted to investigate the major operating variables and optimization of experimental conditions. The predicted values of responses obtained using the response function were in accordance with the experimental data. Under optimized conditions, removal of about 99.99% of Ni(II) was achieved. Langmuir isotherm and pseudo-second-order kinetics best interpreted the experimental data. The overall process was feasible, spontaneous, and endothermic in nature. The high correlation coefficient (R2) values of the linear method of analysis established its superiority over a nonlinear method for the present system. © 2019 American Society of Civil Engineers.